Penerapan Aturan Ganti Rugi bagi Karyawan Kontrak akibat Pengakhiran Perjanjian sebelum Berakhirnya Masa Perjanjian di PT. SII berdasarkan Undang-Undang Ketenagakerjaan - Nurhayani Nurhayani; Rizka Amelia Azis; Elok Hikmawati (Jurnal Hukum Lex Generalis, 2026)
This research aims to examine the implementation of Article 62 of Law Number 13 of 2003 concerning Labor, which regulates the obligation to provide compensation by the party that unilaterally terminates a Fixed-Term Employment Agreement (PKWT) before its expiration. This study employs a normative-empirical legal method through a qualitative approach, combining literature review and field research. Although the compensation provision is intended to protect workers, it often creates an imbalance for employers when PKWT employees who resign unilaterally are unwilling or unable to pay the required compensation. The findings indicate that PT. SII consistently applies the compensation mechanism based on Article 62 of the Labor Law, utilizing orderly administrative procedures—ranging from the submission of resignation letters and negotiations on the ability to pay to the drafting of statements that serve as the basis for payroll deductions. Furthermore, this research compares two PKWT legal regimes: under Law Number 13 of 2003 and post-Job Creation Law via Government Regulation Number 35 of 2021 revealing significant changes regarding PKWT duration limits and the introduction of "compensation pay" as new instrument. If a worker refuses to pay the compensation, the company may pursue legal remedies progressively through bipartite and tripartite scheme, up to filing lawsuit in Industrial Relations Court.